2011
DOI: 10.1088/1468-6996/12/2/025002
|View full text |Cite
|
Sign up to set email alerts
|

Tuning optical properties of poly(3-hexylthiophene) nanoparticles through hydrothermal processing

Abstract: Poly(3-hexylthiophene) (P3HT) nanoparticles (NPs) were prepared by a reprecipitation method. Hydrothermal processing applied external pressure to the pristine P3HT NPs at temperatures ranging from 60 to 150• C. Optical absorption and photoluminescence (PL) spectra for the hydrothermally treated P3HT NPs varied markedly with the processing temperature. With increasing treatment temperature, the absorption peak broadened and the peak position shifted from 510 to 623 nm; moreover, the intensity ratio of the 0-1 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 31 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…In contrast, Raman spectroscopy is a natural probe for interrogating the structural and morphological characteristics of conjugated polymers and their transient states and has been used extensively to characterize both amorphous and aggregated polymers and polymer-based materials. Conjugated polymers generally have strong Raman activity along in-phase, intra-ring CC and C–C stretching modes that results from large structural displacements between the ground and excited/charged states . Raman spectroscopy has been demonstrated to be a sensitive probe of intermolecular order, particularly in conjugated materials, with a few groups reporting morphological dependencies in the steady-state Raman spectra of P3HT films. , Significant differences have been observed in the Raman spectra of P3HT films characterized by different degrees of polymer regioregularity, annealing, and doping with electron acceptors (PCBM); lower CC stretching frequencies are consistently observed with films prepared under conditions that promote assembly of ordered polymer domains (e.g., lamellar stacking). ,, A general explanation for these variations is that higher intra molecular conformational order is obtained with higher inter molecular ordering, resulting in an overall greater delocalization within constituent polymers and corresponding softening of the CC stretch potential. , The sensitivity of this mode to variations in intermolecular order and excited-state or charge (de)­localization implies that time-resolved Raman spectroscopy should provide a valuable probe of the nature of photoinduced transient states in polymer materials.…”
mentioning
confidence: 99%
“…In contrast, Raman spectroscopy is a natural probe for interrogating the structural and morphological characteristics of conjugated polymers and their transient states and has been used extensively to characterize both amorphous and aggregated polymers and polymer-based materials. Conjugated polymers generally have strong Raman activity along in-phase, intra-ring CC and C–C stretching modes that results from large structural displacements between the ground and excited/charged states . Raman spectroscopy has been demonstrated to be a sensitive probe of intermolecular order, particularly in conjugated materials, with a few groups reporting morphological dependencies in the steady-state Raman spectra of P3HT films. , Significant differences have been observed in the Raman spectra of P3HT films characterized by different degrees of polymer regioregularity, annealing, and doping with electron acceptors (PCBM); lower CC stretching frequencies are consistently observed with films prepared under conditions that promote assembly of ordered polymer domains (e.g., lamellar stacking). ,, A general explanation for these variations is that higher intra molecular conformational order is obtained with higher inter molecular ordering, resulting in an overall greater delocalization within constituent polymers and corresponding softening of the CC stretch potential. , The sensitivity of this mode to variations in intermolecular order and excited-state or charge (de)­localization implies that time-resolved Raman spectroscopy should provide a valuable probe of the nature of photoinduced transient states in polymer materials.…”
mentioning
confidence: 99%
“…For nanoparticles prepared by the solvent evaporation method, polymer aggregation can be controlled by the choice of “oil” phase or solvent mixture . Polymer aggregation may also be adjusted postfabrication by hydrothermal annealing of the aqueous nanoparticle dispersion. , …”
Section: Fabricating Polymer Nanoparticlesmentioning
confidence: 99%
“…In our work, we have applied time-resolved Raman spectroscopy to interrogate how material microstructure impacts the dynamics of charge separation, specifically probing the dynamics of polaron-pair formation in nanoparticle aggregates of P3HT. Like P3HT films prepared for device applications through spin-coating, nanoparticles prepared by polymer reprecipitation (50–200 nm in size) have mixed microstructures that can be recognized readily from their steady-state absorption and Raman spectra. , Additionally, Clafton and Kee demonstrated that nanoparticles and films have qualitatively similar photoinduced dynamics . Given these photophysical similarities with films, suspensions of nanoparticles are convenient samples for multipulse laser experiments (such as time-resolved FSRS) as they have increased optical density compared to films and are highly robust to interactions with laser pulses with high peak powers.…”
mentioning
confidence: 99%